Strategi Manajemen SDM dalam Menangani Burnout Karyawan: Literature Review terhadap Pendekatan Kesejahteraan Karyawan - Orchida Ramadhania Fathumita; Kukuh Harianto (Master of Management FEB ULM, 2026)
This study aims to examine Human Resource Management (HRM) strategies in addressing employee burnout through a literatur riview of 21 national and international articles published between 2021 and 2025. Burnout is understood as an individual problem caused by high workloads, role ambiguity, lack of emotional support, and weak HR policies. Using a descriptive qualitative approach, this study analyzes key themes covering the causes of burnout, HR strategies, and approaches to work well-being. The Study result indicate that strategies such as work-life balance programs, organizatonal support, HR development,and emotional intelligence training are highly effective in reducing burnout levels. These strategies support mental health, increase employee productivity, and support organizational sustainability. This research provides a practical contribution to organizations in developing HR policies oriented towards employee well – being